2017
DOI: 10.4236/ajps.2017.87111
|View full text |Cite
|
Sign up to set email alerts
|

Health-Benefit Assets of Different Indian Processed Teas: A Comparative Approach

Abstract: A comparative deliberation has been considered among three Indian processed teas (black, green and white) in respect to their prevalence of some secondary metabolites, antioxidant ability (ABTS and DPPH assay), nutritional properties, inorganic elemental profile and bactericidal efficiency. Green and white tea, incidence of total phenol, total flavonoids, proanthocyanidins and tannin are higher than the black. ABTS and DPPH study reveals lower IC 50 occurred in Green tea. Green tea is enriched in Na, Fe, Mg, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
2
0
3
Order By: Relevance
“…[60][61][62][63]. Aynı zamanda fenolik bileşikler oksidasyonla yapraklardaki renk değişiminden sorumlu olan yeni bileşiklere dönüşmektedir [64]. Bazı araştırmacılar ise, antimikrobiyal etkinin sodyum glutamat ve riboz gibi intra selülar maddelerin salınımından ve hücre duvarı ile hücre membranının geçirgenliğine zarar vermelerinden kaynaklandığını; ayrıca Cu, Mg, Zn ve Fe gibi minerallerin oluşumunun hızlanmasıyla da antimikrobiyal etkinin arttığını bildirmektedirler [65].…”
Section: Mikrobiyolojik Analizlerunclassified
See 2 more Smart Citations
“…[60][61][62][63]. Aynı zamanda fenolik bileşikler oksidasyonla yapraklardaki renk değişiminden sorumlu olan yeni bileşiklere dönüşmektedir [64]. Bazı araştırmacılar ise, antimikrobiyal etkinin sodyum glutamat ve riboz gibi intra selülar maddelerin salınımından ve hücre duvarı ile hücre membranının geçirgenliğine zarar vermelerinden kaynaklandığını; ayrıca Cu, Mg, Zn ve Fe gibi minerallerin oluşumunun hızlanmasıyla da antimikrobiyal etkinin arttığını bildirmektedirler [65].…”
Section: Mikrobiyolojik Analizlerunclassified
“…Çay yapraklarında bulunan fenolik bileşikler (kateşinler ve metil-ksantin alkaloidler), kafein, teabromin, ve teofilin antibakteriyel etkiye sahip bileşikler olup, bu etki çay yapraklarının oksidasyon-fermentasyon süresinin uzamasına bağlı olarak azalmaktadır. Bu açıdan değerlendirildiğinde yeşil çayın, siyah çaya göre daha güçlü antibakteriyel etkisi bulunmakta [62,[66][67], ancak siyah çay yapraklarındaki tanen ve flavonoidler bu etkiyi bazı durumlarda arttırabilmektedirler [64]. En yüksek antimikrobiyal etkiyi göstermesi beklenen fermenteokside olmamış beyaz çay yapraklarında, yaprakların soldurulması esnasında enzimatik inaktivasyon gerçekleşmediğinden polifenoller daha az düzeyde okside olmakta ve renk değişimi için oksidasyon enzimleri aktif biçimde çalışmaya devam etmektedir [64,[68][69].…”
Section: Mikrobiyolojik Analizlerunclassified
See 1 more Smart Citation
“…In addition to its conventional refreshing ability, in recent years, the value added knowledge of tea health benefit properties have augmented the consumption of tea by health conscious people and increased the demand for quality tea marketing as well. The evidences point out the role of tea consumption in challenging the risk of neurological and cardiovascular disorder, diabetes, various types of cancer, oral disease even glaucoma too (Hayat et al, 2015;Hazra, Saha, et al, 2017;Khan & Mukhtar, 2013; "Tea Advisory Panel, UK"). This increased awareness demand the attention of scientific community for breeding new cultivars with improved yield and quality according to the choice of end users.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence unclosed that the highest levels of catechins found in green tea led to increased antioxidant properties; furthermore, black tea contained secondary polyphenols (theaflavins and thearubigins) that are responsible for high antioxidant potential. Efficient antioxidant properties, which have a role in scavenging free radicals, inhibiting lipid peroxidation, and chelating metal ions, have been identified in black tea (Hazra et al, 2017). It is reported that factory tea waste contains 6.3% of tannic acid, which interferes in protein metabolism and water-soluble phenolic metabolites.…”
Section: Introductionmentioning
confidence: 99%